Electrolytic copper foil and preparation method thereof, and lithium battery

By adding specific additives to electrolyze the copper foil preparation process of lithium-ion batteries, the problem of safety hazards of copper foil during the rolling process and during use is solved, and the effect of improving the elongation and conductivity of copper foil is achieved.

CN117987890BActive Publication Date: 2025-02-14EVE ENERGY CO LTD

Patent Information

Application Number
CN202410122292.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-29
Publication Date
2025-02-14
Estimated Expiration
2044-01-29

AI Technical Summary

Technical Problem

During the production process of lithium-ion batteries, copper foil is prone to breaking the belt during rolling, resulting in a decrease in production capacity, and may cause the copper foil to break during charging and discharging during use, posing a safety hazard.

Method used

To the sulfuric acid-copper sulfate solution, add graphene oxide, guar gum, hydroxypropyl methylcellulose, polyethylene glycol, polyethyleneimine and chlorine-containing compounds, as additives, as soluble salts of gold and platinum elements , the electrolytic copper foil is prepared to improve the elongation and conductivity of the copper foil.

Benefits of technology

The elongation and conductivity of the copper foil are improved, the break resistance during the rolling process is enhanced, safety hazards are reduced, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004689489480000071
    Figure BDA0004689489480000071
  • Figure BDA0004689489480000081
    Figure BDA0004689489480000081
Patent Text Reader

Abstract

The present application relates to an electrolytic copper foil and a preparation method thereof and a lithium battery, wherein the electrolytic copper foil contains: a copper content ≥ 99.9wt%, a chlorine content of 100-200μg / g, and further contains: a gold content of 80-200μg / g, and a platinum content of 80-200μg / g. The electrolytic copper foil containing gold and platinum elements can improve the broken belt during the rolling process of lithium-ion batteries and the safety problems during the use of batteries, can improve the elongation, improve the process production efficiency and prevent the occurrence of safety accidents; at the same time, a small amount of gold and platinum is added for better conductivity, which improves the conductivity of the foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolytic copper foil and a preparation method thereof, and a lithium battery. Background Art

[0002] As the negative electrode current collector of lithium-ion batteries, copper foil has excellent ductility, high glossiness, and good performance, and is a key material for the production of lithium-ion batteries. In the process of making lithium-ion batteries, rolling the pole piece can improve the peel strength between the active material and the current collector foil, increase the energy density of the battery cell, reduce the porosity between the active material, conductive agent, and binder inside the pole piece, reduce the resistance of the battery, and ensure the battery performance, density, and thickness consistency of the surface material of the battery pole piece. However, during the cold pressing process, as the energy density increases, the foil becomes thinner and thinner, and the strip will break during the rolling process, affecting production capacity. At the same time, the charging and discharging of the finished battery during use will also cause the copper foil to break, posing a safety hazard. Summary of the invention

[0003] Based on this, it is necessary to provide an electrolytic copper foil and its preparation method and a lithium battery to address the above technical problems, which can improve the elongation of the copper foil, improve the process production efficiency and prevent the occurrence of safety accidents; at the same time, it can also improve the conductivity of the foil.

[0004] In a first aspect, the present application provides an electrolytic copper foil, comprising: a copper content ≥ 99.9wt%, a chlorine content of 100-200μg / g, and further comprising: a gold content of 80-200μg / g, and a platinum content of 80-200μg / g.

[0005] The second aspect also provides a method for preparing the above-mentioned electrolytic copper foil, adding additives to a sulfuric acid-copper sulfate solution, electrolyzing as an electrolyte, and washing and drying the obtained raw foil to obtain the electrolytic copper foil; the additives include graphene oxide, guar gum, hydroxypropyl methylcellulose, polyethylene glycol, polyethyleneimine and chlorine-containing compounds, and the additives also include soluble salts of gold elements and soluble salts of platinum elements.

[0006] In one embodiment, the soluble salt of the gold element is selected from one or more of sodium chloroaurate and potassium gold cyanide. Preferably, the soluble salt of the gold element is selected from potassium gold cyanide.

[0007] In one embodiment, the soluble salt of the platinum element is selected from one or more of platinum acetate and platinum nitrate. Preferably, the soluble salt of the platinum element is selected from platinum nitrate.

[0008] In one embodiment, in the electrolyte, Cu 2+The concentration of copper sulfate is 40-105 g / L, and the concentration of sulfuric acid is 100-200 g / L. Preferably, in the sulfuric acid-copper sulfate solution, Cu 2+ The concentration of argon is 65-90 g / L, and the concentration of sulfuric acid is 120-190 g / L.

[0009] In one embodiment, in the electrolyte, the concentration of graphene oxide is 2-8 mg / L, the concentration of guar gum is 10-18 mg / L, the concentration of gold is 20-50 mg / L, the concentration of platinum is 20-50 mg / L, the concentration of hydroxypropyl methylcellulose is 4-20 mg / L, the concentration of polyethylene glycol is 4-10 mg / L, the concentration of polyethyleneimine is 20-50 mg / L, and the concentration of chlorine-containing compounds is 10-18 mg / L. - The concentration of graphene oxide is 3-8 mg / L, the concentration of guar gum is 12-17 mg / L, the concentration of gold is 20-37 mg / L, the concentration of platinum is 20-45 mg / L, the concentration of hydroxypropyl methylcellulose is 8-15 mg / L, the concentration of polyethylene glycol is 5-10 mg / L, the concentration of polyethyleneimine is 28-40 mg / L, and the concentration of chlorine-containing compounds is 10-40 mg / L. - The concentration is 15-33 mg / L.

[0010] In one embodiment, the molecular weight of the polyethylene glycol is 3000-8000; the molecular weight of the polyethylene imine is 5000-10000. Preferably, the molecular weight of the polyethylene glycol is 3000-6000; the molecular weight of the polyethylene imine is 6000-10000. The chlorine-containing compound is selected from one or more of potassium chloride, sodium chloride, magnesium chloride and calcium chloride.

[0011] In one embodiment, during the electrolysis process, the temperature of the electrolyte is controlled at 40-65°C, and the average current density on the cathode electrode surface is 40-80A / dm 2 .

[0012] In one embodiment, the process of washing the raw foil includes multiple water washings, followed by washing with dilute hydrochloric acid, and then multiple water washings.

[0013] The third aspect of the present invention also provides a lithium battery, comprising the above-mentioned electrolytic copper foil.

[0014] The above introduces the electrolytic copper foil, its preparation method and lithium battery. The electrolytic copper foil prepared above can improve the broken belt during the rolling process of lithium-ion batteries and the safety problems during the use of batteries. Gold and platinum are added during the copper foil production process to improve the elongation, improve the process production efficiency and prevent the occurrence of safety accidents. At the same time, a small amount of gold and platinum are added to improve the conductivity, thereby improving the conductivity of the foil. DETAILED DESCRIPTION

[0015] The electrolytic copper foil and its preparation method and the lithium battery of the present invention are further described below in conjunction with the embodiments:

[0016] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0017] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0018] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0019] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0020] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0021] Unless otherwise specified, the "parts" described in the present invention are all based on parts by weight.

[0022] Example 1

[0023] Add the additive to the sulfuric acid-copper sulfate solution as the electrolyte and conduct the electrolysis at 45°C and 53A / dm 2 Electrolysis is performed at a current density of , and the obtained raw foil is washed and dried to obtain the electrolytic copper foil, specifically, water washing, acid washing, re-water washing, grinding, and baking are performed to obtain the high-ductility electrolytic copper foil;

[0024] In electrolyte:

[0025] Polyethylene glycol with a molecular weight of 4000 and a concentration of 8 mg / L

[0026] Molecular weight of polyethyleneimine is 9000, concentration is 35mg / L

[0027] Hydroxypropyl methylcellulose concentration is 15mg / L

[0028] Cu 2+ The concentration of 65g / L, the concentration of sulfuric acid is 120g / L;

[0029] Chlorine compounds Cl - Concentration 20mg / L

[0030] Graphene oxide concentration 5mg / L

[0031] Guar gum concentration 12mg / L

[0032] The gold concentration of potassium gold cyanide is 20 mg / L

[0033] The platinum concentration of platinum nitrate is 35 mg / L

[0034] Example 2

[0035] Add the additive to the sulfuric acid-copper sulfate solution as the electrolyte and conduct the electrolysis at 55°C and 45A / dm 2 Electrolysis is performed at a current density of , and the obtained raw foil is washed and dried to obtain the electrolytic copper foil, specifically, water washing, acid washing, re-water washing, grinding, and baking are performed to obtain the high-ductility electrolytic copper foil;

[0036] In electrolyte:

[0037] Polyethylene glycol with a molecular weight of 6000 and a concentration of 10 mg / L

[0038] Molecular weight of polyethyleneimine is 8000, concentration is 28mg / L

[0039] Hydroxypropyl methylcellulose concentration is 10mg / L

[0040] Cu 2+ The concentration of sulfuric acid is 80g / L and 180g / L

[0041] Chlorine compounds Cl - Concentration 15mg / L

[0042] Graphene oxide concentration 5mg / L

[0043] Guar gum concentration 12mg / L

[0044] The gold concentration of potassium gold cyanide is 25 mg / L

[0045] The platinum concentration of platinum nitrate is 25 mg / L

[0046] Example 3

[0047] Add the additive to the sulfuric acid-copper sulfate solution as the electrolyte and conduct the electrolysis at 60°C and 70A / dm 2 Electrolysis is performed at a current density of , and the obtained raw foil is washed and dried to obtain the electrolytic copper foil, specifically, water washing, acid washing, re-water washing, grinding, and baking are performed to obtain the high-ductility electrolytic copper foil;

[0048] In electrolyte:

[0049] Polyethylene glycol with a molecular weight of 3000 and a concentration of 5 mg / L

[0050] Molecular weight of polyethyleneimine is 10000, concentration is 35mg / L

[0051] Hydroxypropyl methylcellulose concentration is 8mg / L

[0052] Cu 2+ The concentration of sulfuric acid is 70g / L and 130g / L

[0053] Chlorine compounds Cl - Concentration 30mg / L

[0054] Graphene oxide concentration 8mg / L

[0055] Guar gum concentration 15mg / L

[0056] The gold concentration of potassium gold cyanide is 30 mg / L

[0057] The platinum concentration of platinum nitrate is 20 mg / L

[0058] Example 4

[0059] Add the additive to the sulfuric acid-copper sulfate solution as the electrolyte and conduct the electrolysis at 40°C and 80A / dm 2 Electrolysis is performed at a current density of , and the obtained raw foil is washed and dried to obtain the electrolytic copper foil, specifically, water washing, acid washing, re-water washing, grinding, and baking are performed to obtain the high-ductility electrolytic copper foil;

[0060] In electrolyte:

[0061] Polyethylene glycol with a molecular weight of 5000 and a concentration of 7 mg / L

[0062] Molecular weight of polyethyleneimine is 6000, concentration is 40mg / L

[0063] Hydroxypropyl methylcellulose concentration is 13mg / L

[0064] Cu 2+ The concentration of sulfuric acid is 90g / L and 190g / L

[0065] Chlorine compounds Cl - Concentration 23mg / L

[0066] Graphene oxide concentration 3mg / L

[0067] Guar gum concentration 12mg / L

[0068] The gold concentration of potassium gold cyanide is 37 mg / L

[0069] The platinum concentration of platinum nitrate is 23 mg / L

[0070] Example 5

[0071] Add the additive to the sulfuric acid-copper sulfate solution as the electrolyte and conduct the electrolysis at 45°C and 40A / dm 2 Electrolysis is performed at a current density of , and the obtained raw foil is washed and dried to obtain the electrolytic copper foil, specifically, water washing, acid washing, re-water washing, grinding, and baking are performed to obtain the high-ductility electrolytic copper foil;

[0072] In electrolyte:

[0073] Polyethylene glycol with a molecular weight of 4300 and a concentration of 9 mg / L

[0074] Molecular weight of polyethyleneimine is 5600, concentration is 28mg / L

[0075] Hydroxypropyl methylcellulose concentration is 8mg / L

[0076] Cu 2+ The concentration of sulfuric acid is 85g / L and 175g / L

[0077] Chlorine compounds Cl - Concentration 33mg / L

[0078] Graphene oxide concentration 5mg / L

[0079] Guar gum concentration 17mg / L

[0080] The gold concentration of potassium gold cyanide is 33 mg / L

[0081] The platinum concentration of platinum nitrate is 45 mg / L

[0082] Example 6

[0083] Add the additive to the sulfuric acid-copper sulfate solution as the electrolyte and conduct the electrolysis at 45°C and 40A / dm2 Electrolysis is performed at a current density of , and the obtained raw foil is washed and dried to obtain the electrolytic copper foil, specifically, water washing, acid washing, re-water washing, grinding, and baking are performed to obtain the high-ductility electrolytic copper foil;

[0084] In electrolyte:

[0085] Polyethylene glycol with a molecular weight of 4300 and a concentration of 4 mg / L

[0086] Molecular weight of polyethyleneimine is 5600, concentration is 20mg / L

[0087] Hydroxypropyl methylcellulose concentration is 4 mg / L

[0088] Cu 2+ The concentration of sulfuric acid is 40g / L and the concentration of sulfuric acid is 100g / L

[0089] Chlorine compounds Cl - Concentration 10mg / L

[0090] Graphene oxide concentration 2mg / L

[0091] Guar gum concentration 10mg / L

[0092] The gold concentration of potassium gold cyanide is 20 mg / L

[0093] The platinum concentration of platinum nitrate is 20 mg / L

[0094] Example 7

[0095] Add the additive to the sulfuric acid-copper sulfate solution as the electrolyte and conduct the electrolysis at 65°C and 45A / dm 2 Electrolysis is performed at a current density of , and the obtained raw foil is washed and dried to obtain the electrolytic copper foil, specifically, water washing, acid washing, re-water washing, grinding, and baking are performed to obtain the high-ductility electrolytic copper foil;

[0096] In electrolyte:

[0097] Polyethylene glycol with a molecular weight of 8000 and a concentration of 10 mg / L

[0098] Molecular weight of polyethyleneimine is 10000, concentration is 50mg / L

[0099] Hydroxypropyl methylcellulose concentration is 20mg / L

[0100] Cu 2+ The concentration of sulfuric acid is 105g / L and 200g / L

[0101] Chlorine compounds Cl - Concentration 40mg / L

[0102] Graphene oxide concentration 8mg / L

[0103] Guar gum concentration 18mg / L

[0104] The gold concentration of potassium gold cyanide is 50 mg / L

[0105] The platinum concentration of platinum nitrate is 50 mg / L

[0106] Comparative Example 1

[0107] The lithium battery copper foil was prepared by the same method as in Example 1, without adding potassium gold cyanide and platinum nitrate, and other components and data remained unchanged.

[0108] Comparative Example 2

[0109] The lithium battery copper foil was prepared by the same method as in Example 1 without adding platinum nitrate, and other components and data remained unchanged.

[0110] Comparative Example 3

[0111] The lithium battery copper foil was prepared by the same method as in Example 1 without adding potassium gold cyanide, and other components and data remained unchanged.

[0112] Experimental results: The contents of various elements in the electrolytic copper foils obtained in the above examples and comparative examples were measured, and the results are shown in the following table:

[0113]

[0114]

[0115] The tensile strength and elongation of the electrolytic copper foils prepared in Examples 1-7 and Comparative Examples 1-3 were tested. The test results are shown in the following table:

[0116] Group Tensile strength(MPa) Elongation(%) Resistivity(Ωm) Example 1 540 11.8 1.63*10^-8 Example 2 530 11.3 1.65*10^-8 Example 3 490 10.4 1.68*10^-8 Example 4 510 9.9 1.66*10^-8 Example 5 570 10.2 1.67*10^-8 Example 6 505 10.3 1.66*10^-8 Example 7 512 10.7 1.65*10^-8 Comparative Example 1 410 5.4 1.72*10^-8 Comparative Example 2 430 7.3 1.70*10^-8 Comparative Example 3 450 8.1 1.69*10^-8

[0117] From the table above, we can see that the current density is 40-80A / dm at a temperature of 40-65°C. 2 Under these conditions, the tensile strength and elongation of the electrolytic copper foil prepared with gold and platinum additives are greatly improved, the electrical conductivity is reduced, and the electrical conductivity is improved.

[0118] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0119] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. An electrolytic copper foil, comprising: a copper content of ≥99.9wt%, a chlorine content of 100-200μg / g, characterized in that: It also contains: gold element content of 80-200μg / g, and platinum element content of 80-200μg / g.

2. A method for preparing the electrolytic copper foil according to claim 1, comprising: Additives are added to a sulfuric acid-copper sulfate solution, which is used as an electrolyte for electrolysis, and the obtained raw foil is washed and dried to obtain the electrolytic copper foil; the additives include graphene oxide, guar gum, hydroxypropyl methylcellulose, polyethylene glycol, polyethyleneimine and chlorine-containing compounds, and the additives also include soluble salts of gold and platinum.

3. The preparation method according to claim 2, characterized in that: The soluble salt of the gold element is selected from one or more of sodium chloroaurate and potassium gold cyanide.

4. The preparation method according to claim 2, characterized in that: The soluble salt of the platinum element is selected from one or more of platinum acetate and platinum nitrate.

5. The preparation method according to claim 2, characterized in that: In the electrolyte, Cu 2+ The concentration of argon is 40-105 g / L, and the concentration of sulfuric acid is 100-200 g / L.

6. The preparation method according to claim 2, characterized in that: In the electrolyte, the concentration of graphene oxide is 2-8 mg / L, the concentration of guar gum is 10-18 mg / L, the concentration of gold element is 20-50 mg / L, the concentration of platinum element is 20-50 mg / L, the concentration of hydroxypropyl methylcellulose is 4-20 mg / L, the concentration of polyethylene glycol is 4-10 mg / L, the concentration of polyethyleneimine is 20-50 mg / L, and the concentration of chlorine-containing compounds is 10-20 mg / L. - The concentration is 10-40 mg / L.

7. The preparation method according to claim 2, characterized in that: The molecular weight of the polyethylene glycol is 3000-8000; the molecular weight of the polyethylene imine is 5000-10000.

8. The preparation method according to claim 2, characterized in that: During the electrolysis process, the temperature of the electrolyte is controlled at 40-65°C, and the average current density on the cathode electrode surface is 40-80A / dm 2 .

9. The preparation method according to claim 2, characterized in that: The process of washing the raw foil includes multiple water washes, followed by dilute hydrochloric acid washes, and then multiple water washes.

10. A lithium battery, characterized in that: The invention comprises the electrolytic copper foil as claimed in claim 1.

Citation Information

Patent Citations

  • Electrolytic copper foil and preparation method thereof

    CN112981473A

  • Copper-nickel-cobalt alloy foil process

    CN114059105A

Cited By

  • Electrolytic copper foil and preparation method therefor, and lithium battery

    EP4768635A1

  • Electrolytic copper foil and preparation method therefor, and lithium battery

    WO2025161253A1